Pitching early for CCUS research and development in oil & gas industry: A well thought endeavor - Tewari, R.D. (Society of Petroleum Engineers, 2021)
The oil and gas industry, a highly technical industry, involves a collaboration of various disciplines of science and technology from exploration to production and utilization of the products. Continuous research and technology developments have improved the success of the industry. Oil and Gas will continue to play important role in the total energy mix due to their affordability and easiness of use. The infrastructure and facilities viz, drilling rigs, pipeline, casing and tubular, platforms and chemical produced from other industries also contribute significant greenhouse gas (GHG) emission. Increased use of oil & gas is causing the emission of GHG in the atmosphere causing temperature rise of the earth which is a major cause for climate change. The increasing demand for natural gas is necessitating the development of giant contaminated gas fields which will further increase GHG production significantly. Natural gas would be the transition fuel from conventional to renewable energy sources. Climate science is understood, and experts are of the view that current and enhanced future emissions of GHG will have a catastrophic effect on the environment. It has to be controlled and produced contaminated gases need to be stored safely and utilized for humanity. Improvement in energy efficiency and environmental sustainability by reduction of greenhouse gas emissions from the industrial operations as well as from energy use by consumers is picking up. Carbon capture, separation, transportation, storage, and utilization has started at a small scale. There is an urgent need to improve yesterdayâs performance and meet tomorrowâs challenge in CCUS in the petroleum industry. Fundamental research for capturing, utilization and storage of GHG has to be enhanced for improvising the processes. It is a fact that technology stimulates science, science stimulates technology, and both stimulate the efficiency of the process. Because of this, success mantra and objective for better performance, oil and gas companies are investing and pursuing research and development for controlling and managing the carbon capture utilization and storage (CCUS). This paper discusses the result of active Research and Development of CCUS which is being pursued for the last decades for fundamental issues of separation of carbon dioxide, transportation, subsurface storage physics & chemistry and utilization of the CO2 into usable products. Scientific results and findings of basic and applied research for better efficiency and cost-effectiveness of the products like precipitated calcium carbonate (PCC), alcohols and methane generation by Methanogenesis. Supercritical behavior of CO2 in subsurface, geomechanical and geochemical changes during and after storage, enhancing trapping mechanism, the effect of H2S on CO2 storage and understanding the science of contaminant separation and areas of improvement in methodologies will be presented and highlighted. Â© 2021, Society of Petroleum Engineers.